Negative active material and preparation method thereof, negative pole piece, battery and power utilization device

By using a combination of resin-based carbon skeleton and active material units in the negative electrode active material, the problem of large volume changes in the charge and discharge process and excessive reaction with the electrolyte is solved, and the stability of the material and the circulation of the battery are achieved. Performance improvement.

CN119495733APending Publication Date: 2025-02-21REPT BATTERO ENERGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702679.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing prelithiated silicon carbon negative electrode materials have large volume changes during charging and discharging, which can easily lead to rupture of the electrode structure, and excessive reaction between the Li-Si structure and electrolyte, resulting in attenuation of the battery capacity and poor stability in water and air.

Method used

Using a negative electrode active material that combines a resin-based carbon skeleton with an active material unit, the resin-based carbon skeleton has a hole connected to the interior. The active material unit includes a -O-Li-Si structure connected to the hole wall surface and a hole inside. Nickel metal particles form a stable structure through heat treatment.

Benefits of technology

This material can suppress the volume expansion of the silicon material without additional coating, reduce excessive consumption of electrolyte, improve the water oxygen stability of prelithiated silicon carbon materials, reduce the capacity attenuation of the battery, and improve the circulation of the battery stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495733A_ABST
    Figure CN119495733A_ABST
Patent Text Reader

Abstract

The invention relates to a negative active material and a preparation method thereof, a negative pole piece, a battery and an electric device. The negative electrode active material comprises: a resin-based carbon skeleton, the surface of which is provided with a pore channel communicated to the interior of the resin-based carbon skeleton; the active substance unit is arranged in the pore channel of the resin-based carbon skeleton, and the active substance unit comprises an-O-Li-Si structure connected with the wall surface of the pore channel and nickel metal particles located in the pore channel. According to the negative electrode active material provided by the invention, a stable-O-Li-Si structure improves the water-oxygen stability of the pre-lithiated silicon carbon material, a resin-based carbon skeleton plays a role in protecting an active substance unit, under the condition that coating is not needed, the volume expansion of a silicon material is inhibited, the consumption of an electrolyte is reduced, and the conductivity is improved by nickel metal; and meanwhile, the-O-Li-Si structure can provide a continuous and stable lithium supplement site, so that the capacity fading of the battery is reduced, and the cycling stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode sheet, a battery, and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics, energy storage devices, and electric vehicles due to their high energy density, long cycle life, and low self-discharge rate.

[0003] Silicon-carbon negative electrode materials combine the high theoretical specific capacity of silicon with the good conductivity and structural stability of carbon materials, and can meet the requirements of high energy density lithium-ion batteries. In the manufacturing process of negative electrode materials, the pre-lithiation process is introduced to pre-introduce lithium ions into silicon-carbon materials to alleviate the problem of excessive lithium ion consumption during the first charging process, thereby improving the first coulombic efficiency of the battery.

[0004] However, the current pre-lithiation silicon-carbon negative electrode materials have the following problems: (1) The volume of silicon materials changes greatly during the charge and discharge process, which can easily lead to the rupture of the electrode structure and cause capacity decay; (2) The Li-Si structure can react with the electrolyte. When the Li-Si structure is in direct contact with the electrolyte, it leads to excessive consumption of the electrolyte, which in turn causes battery capacity decay; (3) The pre-lithiation material has poor stability in water and air.

[0005] In traditional technology, coating is often used to protect pre-lithiation silicon-carbon negative electrode materials and inhibit the expansion of silicon materials. However, there is a problem of poor coating effect, complex process flow and high cost. Summary of the invention

[0006] Based on this, it is necessary to provide a negative electrode active material and its preparation method, a negative electrode plate, a battery, and an electrical device that can inhibit the volume expansion of silicon materials without additional coating, reduce excessive consumption of electrolyte, and improve the water and oxygen stability of pre-lithiation silicon-carbon materials, thereby reducing the capacity attenuation of the battery and improving the cycle stability of the battery.

[0007] The first aspect of the present application provides a negative electrode active material, which includes: a resin-based carbon skeleton, a surface of which is provided with pores connected to the interior of the resin-based carbon skeleton; and an active substance unit, which is arranged in the pores of the resin-based carbon skeleton, and the active substance unit includes an -O-Li-Si structure connected to the surface of the pore wall and nickel metal particles located inside the pore.

[0008] In some embodiments, the average pore size of the pores is 0.5 nm to 6 nm.

[0009] In some embodiments, the resin-based carbon framework is a hard carbon material.

[0010] The second aspect of the present application provides a method for preparing a negative electrode active material, which comprises the following steps: S1, mixing a resin monomer, a nickel salt, a silicon powder and an initiator in a solvent, filtering and drying after the reaction to obtain a silicon-carbon material precursor; S2, mixing the silicon-carbon material precursor and lithium hydroxide in a solvent or a buffer solution with a pH of 8 to 10, filtering and drying after the reaction to obtain a pre-lithiated silicon-carbon material precursor; S3, heat-treating the pre-lithiated silicon-carbon material precursor, cooling, and obtaining a negative electrode active material; wherein the negative electrode active material comprises a resin-based carbon skeleton and an active substance unit, the surface of the resin-based carbon skeleton is provided with pores connected to the interior of the resin-based carbon skeleton, the active substance unit is arranged in the pores of the resin-based carbon skeleton, and the active substance unit comprises an -O-Li-Si structure connected to the surface of the pore wall and nickel metal particles located inside the pore.

[0011] In some embodiments, in step S1, the mass ratio of silicon powder to resin monomer is (0.2:1) to (4:1).

[0012] In some embodiments, in step S1, the mass ratio of silicon powder to nickel salt is (1:1) to (10:1).

[0013] In some embodiments, in step S1, the reaction temperature is 100°C to 150°C, and the reaction time is 3h to 5h.

[0014] In some embodiments, in step S2, the mass ratio of nickel salt to lithium hydroxide in the silicon-carbon material precursor is (0.9:1) to (2:1).

[0015] In some embodiments, in step S3, the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially, the temperature of the pre-oxidation treatment is 150°C to 300°C, the temperature of the carbonization treatment is 550°C to 750°C, and the heating rate of the carbonization treatment is 1°C / min to 1.5°C / min.

[0016] In some embodiments, in step S3, the cooling rate is 1°C / min to 2°C / min.

[0017] The third aspect of the present application provides a negative electrode plate, which includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.

[0018] A fourth aspect of the present application provides a battery, which includes the negative electrode plate provided by the third aspect.

[0019] A fifth aspect of the present application provides an electrical device, which includes the battery provided by the fourth aspect.

[0020] Compared with the traditional technology, this application has at least the following beneficial effects:

[0021] The negative electrode active material provided by the present application has an active material unit located in the pores of the resin-based carbon skeleton. The stable -O-Li-Si structure in the active material unit is connected to the surface of the pore wall, which improves the water and oxygen stability of the pre-lithiation silicon-carbon material. The resin-based carbon skeleton protects the active material unit inside it. On the one hand, it can reduce storage, transportation and processing costs before packaging the battery; on the other hand, without the need for additional coating, it inhibits the volume expansion of the silicon material and reduces excessive consumption of the electrolyte. Nickel metal improves the conductivity of the active material unit. At the same time, the -O-Li-Si structure can provide a continuous and stable lithium replenishment site, thereby reducing the capacity decay of the battery and improving the cycle stability of the battery.

[0022] The present application provides a method for preparing a negative electrode active material, which first starts a polymerization reaction by mixing a resin monomer with a nickel salt and silicon powder, wherein the nickel salt and silicon powder are physically adsorbed on the resin, and the nickel salt and silicon are uniformly loaded on the resin, so that the nickel salt can provide uniform pre-lithiation active sites to obtain a silicon-carbon material precursor; then the silicon-carbon material precursor is mixed with lithium hydroxide, and the resin material is etched so that the resin material has a pore structure connected to the interior by the surface, and the pore structure also provides a holding space for the nickel salt and silicon, and lithium hydroxide is loaded on the nickel salt to obtain a pre-lithiation silicon-carbon material precursor; finally, the pre-lithiation silicon-carbon material precursor is heat-treated, and during this process, the resin material is carbonized. A resin-based carbon skeleton is formed, and lithium ions are combined with silicon and oxygen atoms to form a stable -O-Li-Si structure on the pore wall of the resin-based carbon skeleton, which improves the water-oxygen stability of the pre-lithiation silicon-carbon material. The resin-based carbon skeleton protects the internal active material units. On the one hand, it can reduce storage, transportation and processing costs before packaging the battery; on the other hand, it inhibits the volume expansion of the silicon material and reduces excessive consumption of the electrolyte. The nickel salt is reduced to nickel metal particles located in the pores. The nickel metal improves the conductivity of the active material unit. At the same time, the -O-Li-Si structure can provide a continuous and stable lithium replenishment site, thereby reducing the capacity decay of the battery and improving the cycle stability of the battery. Therefore, the preparation method of the negative electrode active material provided by the present application, the resin-based carbon skeleton finally formed is a structure formed by heat treatment of a porous resin, and the protective effect can be achieved without additional coating, which simplifies the process flow and saves costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the structure of the negative electrode active material in one embodiment of the present application.

[0024] Figure 2 Schematic diagram of the structure of the active substance unit in one embodiment of the present application.

[0025] Figure 3 Schematic diagram of a process for preparing a negative electrode active material in one embodiment of the present application.

[0026] 1. Negative electrode active material;

[0027] 10. Resin-based carbon skeleton; 11. Pores;

[0028] 20. Active substance unit. DETAILED DESCRIPTION

[0029] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0030] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0031] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0032] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0033] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0034] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0035] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0036] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0037] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0038] like Figure 1 and Figure 2 As shown, the first aspect of the present application provides a negative electrode active material 1, which includes a resin-based carbon skeleton 10 and an active material unit 20. The surface of the resin-based carbon skeleton 10 is provided with a pore 11 connected to the interior of the carbon skeleton. The active material unit 20 is arranged in the pore 11 of the resin-based carbon skeleton 10, and the active material unit 20 includes an -O-Li-Si structure connected to the wall surface of the pore 11 and nickel metal particles located inside the pore 11.

[0039] Herein, "resin-based carbon skeleton" refers to the skeleton structure obtained by carbonizing the resin material after heat treatment.

[0040] The negative electrode active material 1 provided in the present application has an active material unit 20 located in the pore 11 of the resin-based carbon skeleton 10. The stable -O-Li-Si structure in the active material unit 20 is connected to the wall surface of the pore 11, which improves the water and oxygen stability of the pre-lithiation silicon-carbon material. The resin-based carbon skeleton 10 protects the active material unit 20 inside it. On the one hand, it can reduce the storage, transportation and processing costs before packaging the battery; on the other hand, without the need for additional coating, the volume expansion of the silicon material is suppressed, and the excessive consumption of the electrolyte is reduced. The nickel metal improves the conductivity of the active material unit 20. At the same time, the -O-Li-Si structure can provide a continuous and stable lithium replenishment site, thereby reducing the capacity decay of the battery and improving the cycle stability of the battery.

[0041] In some embodiments, the average pore size of the pore 11 is 0.5nm to 6nm, including but not limited to 0.5nm, 1nm, 2nm, 3nm, 4nm, 5nm, and 6nm; by adjusting the average pore size of the pore 11 to within the above range, the penetration of electrolyte molecules into the resin-based carbon skeleton 10 under natural conditions can be reduced, the reaction between the Li-Si structure and the electrolyte can be reduced, and excessive consumption of the electrolyte can be prevented, thereby improving the cycle performance of the battery.

[0042] Furthermore, the average pore size of the pores 11 is 1 nm to 2 nm. The average diameter of the electrolyte solvent molecules is generally between 0.4 nm and 0.8 nm. When the average pore size of the pores 11 is within the above range, it can effectively prevent the electrolyte molecules from penetrating into the resin-based carbon skeleton 10 in a natural state, prevent excessive consumption of the electrolyte, and further improve the cycle performance of the battery.

[0043] In some of the embodiments, the resin-based carbon skeleton 10 is a hard carbon material. Therefore, on the one hand, without affecting the electron transmission and ion transmission of the material, the resin-based carbon skeleton 10 provides protection for the -O-Li-Si core structure to prevent it from having side reactions with air and electrolyte, and provides complete structural support and electrical connection for silicon particles during the battery cycle; on the other hand, the silicon material is dispersed in the hard carbon structure of the resin-based carbon skeleton 10 in the form of active material units 20, which can greatly reduce the expansion of the pole piece during the lithium insertion stage, ensure the mechanical stability of the material and the pole piece, and prevent the battery capacity from rapidly decaying. In addition, the hard carbon structure of the resin-based carbon skeleton 10 can also provide a certain lithium insertion gram capacity, thereby improving the capacity performance of the battery.

[0044] The second aspect of the present application provides a method for preparing a negative electrode active material, such as Figure 3 As shown, the preparation method comprises the following steps:

[0045] S1. Mixing resin monomer, nickel salt, silicon powder and initiator in a solvent, filtering and drying after reaction, to obtain a silicon-carbon material precursor.

[0046] S2, mixing the silicon-carbon material precursor with lithium hydroxide in a solvent or a buffer solution with a pH of 8 to 10, filtering and drying after the reaction, to obtain a pre-lithiated silicon-carbon material precursor.

[0047] S3. Heat-treating the pre-lithiated silicon-carbon material precursor and cooling it to obtain a negative electrode active material.

[0048] The prepared negative electrode active material 1 is as follows Figure 1 and Figure 2 As shown, the negative electrode active material 1 includes a resin-based carbon skeleton 10 and an active material unit 20. The surface of the resin-based carbon skeleton 10 is provided with a pore 11 connected to the interior of the resin-based carbon skeleton 10. The active material unit 20 is arranged in the pore 11. The active material unit 20 includes an -O-Li-Si structure connected to the wall surface of the pore 11 and nickel metal particles located inside the pore 11.

[0049] The present application provides a method for preparing a negative electrode active material, which first starts a polymerization reaction by mixing a resin monomer with a nickel salt and silicon powder, wherein the nickel salt and silicon powder are physically adsorbed on the resin, and the nickel salt and silicon are uniformly loaded on the resin, so that the nickel salt can provide uniform pre-lithiation active sites to obtain a silicon-carbon material precursor; then the silicon-carbon material precursor is mixed with lithium hydroxide, and the resin material is etched so that the resin material has a pore structure connected to the interior by the surface, and the pore structure also provides a holding space for the nickel salt and silicon, and lithium hydroxide is loaded on the nickel salt to obtain a pre-lithiation silicon-carbon material precursor; finally, the pre-lithiation silicon-carbon material precursor is heat-treated, and during this process, the resin material is carbonized to form a resin-based carbon Skeleton 10, lithium ions combine with silicon and oxygen atoms to form a stable -O-Li-Si structure on the wall of the pore 11 of the resin-based carbon skeleton 10, which improves the water and oxygen stability of the pre-lithiation silicon-carbon material. The resin-based carbon skeleton 10 protects the internal active material unit 20. On the one hand, it can reduce the storage, transportation and processing costs before packaging the battery; on the other hand, it inhibits the volume expansion of the silicon material and reduces the excessive consumption of the electrolyte. The nickel salt is reduced to nickel metal particles located in the pore 11. The nickel metal improves the conductivity of the active material 20 unit. At the same time, the -O-Li-Si structure can provide a continuous and stable lithium replenishment site, thereby reducing the capacity decay of the battery and improving the cycle stability of the battery.

[0050] Therefore, in the preparation method of the negative electrode active material 1 provided in the present application, the resin-based carbon skeleton 10 finally formed is a structure formed by heat-treating a porous resin, and can achieve a protective effect without the need for additional coating, thereby simplifying the process flow and saving costs.

[0051] In some embodiments, in step S1, the mass ratio of silicon powder to resin monomer is (0.2: 1) to (4: 1), including but not limited to 0.2: 1, 0.4: 1, 0.6: 1, 0.8: 1, 1: 1, 1.2: 1, 1.4: 1, 1.6: 1, 1.8: 1, 2: 1, 3.2: 1, 3.4: 1, 3.6: 1, 3.8: 1, 4: 1. Within the above mass ratio range, the formation of the resin-based carbon skeleton 10 can be ensured while ensuring 1 gram capacity of the negative electrode active material.

[0052] In some embodiments, in step S1, the mass ratio of silicon powder to nickel salt is (1:1) to (10:1), including but not limited to 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1. Within the above mass ratio range, the first coulombic efficiency is improved and the formation of the resin-based carbon skeleton 10 is guaranteed.

[0053] In some embodiments, in step S1, the resin monomer includes one or more of acrylic acid, methacrylic acid, acrylamide, aminomethyl methacrylate, diethyl vinylphosphonate and 3-mercaptoacrylic acid.

[0054] In some embodiments, in step S1, the nickel salt includes one or more of nickel nitrate, nickel acetate, nickel sulfate and nickel ethylenediaminetetraacetate.

[0055] In some embodiments, in step S1, the particle size of the silicon powder is 1 nm to 100 nm.

[0056] In some embodiments, in step S1, the solvent includes one of deionized water, ethanol, isopropanol, acetone, ethyl acetate, N-methylpyrrolidone, tetrahydrofuran, and N,N-dimethylformamide.

[0057] In some embodiments, in step S1, the initiator includes one of azobisisobutyronitrile (AIBN), azodicarbonamide (V-50) and ammonium persulfate (APS).

[0058] In some embodiments, step S1 is performed under a protective atmosphere, specifically, the protective atmosphere is nitrogen or argon.

[0059] In some embodiments, in step S1, the reaction temperature is 100°C to 150°C, and the reaction time is 3h to 5h. For example, the reaction temperature may be, but not limited to, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C; the reaction time may be, but not limited to, 3h, 3.5h, 4h, 4.5h, 5h. Within the above temperature and time ranges, it can be ensured that the surface of the silicon powder in the silicon-carbon material precursor is fully coated with the resin material, while ensuring the mechanical properties of the material.

[0060] In some embodiments, in step S2, the mass ratio of the nickel salt to the lithium hydroxide in the silicon-carbon material precursor is (0.9: 1) to (2: 1), including but not limited to 0.9: 1, 1: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, 1.6: 1, 1.7: 1, 1.8: 1, 1.9: 1, and 2: 1. Within the above mass ratio range, the lithium hydroxide is loaded on the nickel salt, which can not only ensure the lithium supplement effect, thereby achieving the improvement of the first coulomb efficiency, but also ensure the structural stability of the material during the cycle and ensure the cycle performance of the battery.

[0061] In some embodiments, the buffer solution with a pH of 8 to 10 is an ammonia-ammonium chloride buffer solution. It is understood that the ammonia-ammonium chloride buffer solution can adjust the pH value to be weakly alkaline to prevent damage to the structure of the material, and can be released in the form of NH3 during the subsequent heat treatment without introducing impurities.

[0062] In some embodiments, in step S2, the reaction temperature is 25°C to 40°C, and the reaction time is 1 h to 3 h.

[0063] In some embodiments, in step S3, the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially, the temperature of the pre-oxidation treatment is 150°C to 300°C, the temperature of the carbonization treatment is 550°C to 750°C, and the heating rate of the carbonization treatment is 1°C / min to 1.5°C / min. Exemplarily, the temperature of the pre-oxidation treatment may be, but is not limited to, 150°C, 175°C, 200°C, 225°C, 250°C, 275°C, and 300°C; the temperature of the carbonization treatment may be, but is not limited to, 550°C, 575°C, 600°C, 625°C, 650°C, 675°C, 700°C, 725°C, and 750°C; the heating rate of the carbonization treatment may be, but is not limited to, 1°C / min, 1.1°C / min, 1.2°C / min, 1.3°C / min, 1.4°C / min, and 1.5°C / min.

[0064] It can be understood that during the heat treatment process, the pre-oxidation treatment is first carried out at a lower temperature to ensure the stability of the resin skeleton, and then the carbonization treatment is carried out at a higher temperature, thereby providing a suitable reaction temperature to connect on the surface of the pore wall to form a stable -O-Li-Si structure. At the same time, the step-by-step heating method can reduce the thermal stress of the material and avoid structural damage. In addition, controlling the temperature of the carbonization treatment within the above range is conducive to the formation of a resin-based carbon skeleton with a suitable pore size, so that the resin-based carbon skeleton can not only protect the internal Li-Si structure, but also allow the electrolyte to pass through for lithium ion exchange; controlling the heating rate within the above range, compared with the traditional carbonization heating rate (3℃ / min~5℃ / min), reduces the surface cracks caused by thermal stress and reduces surface defects.

[0065] In some embodiments, the cooling rate is 1°C / min to 2°C / min, including but not limited to 1°C / min, 1.1°C / min, 1.2°C / min, 1.3°C / min, 1.4°C / min, and 1.5°C / min. By controlling the cooling rate within the above range, compared with the traditional cooling rate (3°C / min to 5°C / min), surface cracks caused by thermal stress are reduced and surface defects are reduced.

[0066] In some embodiments, step S3 is performed under a protective atmosphere, specifically, the protective atmosphere is helium or argon.

[0067] The third aspect of the present application provides a negative electrode plate, which includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.

[0068] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is arranged on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the negative electrode active material provided in the first aspect above or the negative electrode active material prepared by the preparation method provided in the second aspect above.

[0069] In some embodiments, the mass percentage of the negative electrode active material in the negative electrode active material layer is 80% to 95%.

[0070] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0071] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), or carboxymethyl chitosan (CMCS).

[0072] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0073] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0074] A fourth aspect of the present application provides a battery, which includes the negative electrode plate provided by the third aspect.

[0075] In some embodiments, the battery comprises a lithium-ion battery. The battery of the present application comprises a battery cell form, a battery module form and a battery pack form.

[0076] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0077] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0078] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0079] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0080] In some embodiments, the positive electrode active material layer may further include a positive electrode active material. The positive electrode active material may be a positive electrode active material for a battery known in the art.

[0081] As an example, when the positive electrode plate is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. Further, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0082] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0083] In some embodiments, based on the total mass of the positive electrode active material layer, the mass proportion of the binder is 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc.

[0084] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0085] In some embodiments, based on the total mass of the positive electrode active material layer, the mass proportion of the conductive agent is 0.8% to 4%, for example, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc.

[0086] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0087] The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0088] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0089] In some of the embodiments, when the battery is a lithium ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0090] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone and diethyl sulfone.

[0091] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0092] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0093] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0094] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0095] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0096] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and the plastic may be polypropylene, polybutylene terephthalate, polybutylene succinate, etc.

[0097] A fifth aspect of the present application provides an electrical device, which includes the battery provided by the fourth aspect.

[0098] Batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0099] The present application will be further described below with reference to specific embodiments and comparative examples.

[0100] Example 1

[0101] Negative electrode active material:

[0102] S1. 8 g of acrylamide, 2 g of methacrylic acid, 2 g of nickel acetate and 2 g of nano silicon powder were mixed with initiator AIBN in deionized water, reacted at 100° C. in a nitrogen atmosphere for 3 h, and then filtered and dried to obtain a silicon-carbon material precursor.

[0103] The total mass ratio of silicon powder to resin monomer is 0.2:1, and the mass ratio of silicon powder to nickel salt is 1:1.

[0104] S2. Mix 7 g of the silicon-carbon material precursor and 1.1 g of lithium hydroxide in an ammonia-ammonium chloride buffer solution with a pH of 9, stir and react at 30° C. for 2 h, and then filter and dry to obtain a pre-lithiated silicon-carbon material precursor.

[0105] Among them, the nickel salt in the silicon-carbon material precursor is 1g, and the mass ratio of the nickel salt in the silicon-carbon material precursor to lithium hydroxide is 0.9:1.

[0106] S3. Under the protection of helium, heat-treat the pre-lithiated silicon-carbon material precursor, cool it, and obtain the negative electrode active material.

[0107] The heat treatment includes a pre-oxidation treatment and a carbonization treatment, which are carried out in sequence. The pre-oxidation treatment is first carried out at 150°C for 3 hours, and then the carbonization treatment is carried out at 600°C for 2 hours. The heating rate of the carbonization treatment is 1°C / min; the cooling rate is 1°C / min.

[0108] Negative electrode:

[0109] According to the mass ratio of negative electrode active material: conductive carbon black (SP): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 80:10:4:6, add appropriate amount of deionized water and mix to form a slurry, which is coated on copper foil, dried at 90°C in vacuum for 12 hours and rolled to form a negative electrode sheet.

[0110] Battery:

[0111] Metal lithium sheets were used as counter and reference electrodes, a 1 mol / L LiPF6 three-component mixed solvent of ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 volume ratio mixed solution was used as the electrolyte, and Celgard 2500 was used as the diaphragm. The cells were assembled into CR2032 button cells in an argon-filled inert gas glove box system.

[0112] Example 2

[0113] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0114] In step S1, 8 g of acrylamide and 2 g of methacrylic acid were replaced with 10 g of aminomethyl methacrylate.

[0115] Example 3

[0116] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0117] The nickel acetate in step S1 was replaced with nickel nitrate.

[0118] Example 4

[0119] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0120] In step S1, the mass ratio of silicon powder to nickel salt is 10:1. That is, the amount of nickel acetate in S1 is 0.2 g, and the amount of lithium hydroxide in S2 is 0.22 g.

[0121] Example 5

[0122] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0123] In step S1, acrylamide is 0.4 g, methacrylic acid is 0.1 g, and the mass ratio of silicon powder to resin monomer is 4:1.

[0124] Example 6

[0125] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0126] In step S2, the amount of lithium hydroxide used is 0.5 g, and the mass ratio of nickel salt to lithium hydroxide is 2:1.

[0127] Example 7

[0128] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0129] In step S3, a pre-oxidation treatment is first performed at 300°C for 3 hours, and then a carbonization treatment is performed at 700°C for 3 hours.

[0130] Example 8

[0131] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0132] In step S1, the reaction temperature is 150° C. and the reaction time is 5 h.

[0133] Example 9

[0134] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0135] In step S3, the heating rate of the carbonization treatment is 1.5°C / min; the cooling rate of the cooling treatment is 2°C / min.

[0136] Example 10

[0137] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0138] In step S3, a pre-oxidation treatment is first performed at 200°C for 3 hours, and then a carbonization treatment is performed at 450°C for 2 hours.

[0139] Embodiment 11

[0140] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0141] In step S3, a pre-oxidation treatment is first performed at 200°C for 3 hours, and then a carbonization treatment is performed at 900°C for 2 hours.

[0142] Example 12

[0143] The negative electrode active material, negative electrode plate and battery provided in this embodiment are basically the same as those in embodiment 1, except that:

[0144] The heating rate of carbonization treatment is 3℃ / min; the cooling rate of cooling is 3℃ / min.

[0145] Comparative Example 1

[0146] Negative electrode active material:

[0147] (1) 8 g of acrylamide, 2 g of methacrylic acid and initiator AIBN were mixed in deionized water to obtain an acrylamide-methacrylic acid copolymer.

[0148] (2) Acrylamide-methacrylic acid copolymer, 2 g of nickel acetate and 2 g of nano-silicon powder were reacted at 100° C. in a nitrogen atmosphere for 3 h, and then filtered and dried to obtain a silicon-carbon material precursor.

[0149] The total mass ratio of silicon powder to resin monomer is 0.2:1, and the mass ratio of silicon powder to nickel salt is 1:1.

[0150] (3) 7 g of the silicon-carbon material precursor and 1.1 g of lithium hydroxide were mixed in an ammonia-ammonium chloride buffer solution with a pH of 9, stirred for reaction at 30° C. for 2 h, and then filtered and dried to obtain a pre-lithiated silicon-carbon material precursor.

[0151] Among them, the nickel salt in the silicon-carbon material precursor is 1g, and the mass ratio of the nickel salt in the silicon-carbon material precursor to lithium hydroxide is 0.9:1.

[0152] (4) Under the protection of helium, the pre-lithiated silicon-carbon material precursor is heat treated and cooled to obtain a negative electrode active material.

[0153] The heat treatment includes a pre-oxidation treatment and a carbonization treatment, which are carried out in sequence. The pre-oxidation treatment is first carried out at 200°C for 3 hours, and then the carbonization treatment is carried out at 600°C for 2 hours. The heating rate of the carbonization treatment is 1°C / min; the cooling rate is 1°C / min.

[0154] Negative electrode:

[0155] According to the mass ratio of negative electrode active material: conductive carbon black (SP): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 80:10:4:6, add appropriate amount of deionized water and mix to form a slurry, which is coated on copper foil, dried at 90°C in vacuum for 12 hours and rolled to form a negative electrode sheet.

[0156] Battery:

[0157] Metal lithium sheets were used as counter and reference electrodes, a 1 mol / L LiPF6 three-component mixed solvent of ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 volume ratio mixed solution was used as the electrolyte, and Celgard 2500 was used as the diaphragm. The cells were assembled into CR2032 button cells in an argon-filled inert gas glove box system.

[0158] Comparative Example 2

[0159] Negative electrode active material:

[0160] S1. Mix 10 g of graphite, 2 g of nickel acetate and 2 g of nano-silicon powder in deionized water, react at 40° C. in a nitrogen atmosphere for 4 h, and then filter and dry to obtain a silicon-carbon material precursor.

[0161] Among them, the ratio of silicon powder to graphite is 0.2:1, and the mass ratio of silicon powder to nickel salt is 1:1.

[0162] S2. Mix 7 g of the silicon-carbon material precursor and 1.1 g of lithium hydroxide in an ammonia-ammonium chloride buffer solution with a pH of 9, stir and react at 30° C. for 2 h, and then filter and dry to obtain a pre-lithiated silicon-carbon material precursor.

[0163] Among them, the nickel salt in the silicon-carbon material precursor is 1g, and the mass ratio of the nickel salt in the silicon-carbon material precursor to lithium hydroxide is 0.9:1.

[0164] S3. Under the protection of helium, heat-treat the pre-lithiated silicon-carbon material precursor, cool it, and obtain the negative electrode active material.

[0165] The heat treatment includes a pre-oxidation treatment and a carbonization treatment, which are carried out in sequence. The pre-oxidation treatment is first carried out at 200°C for 3 hours, and then the carbonization treatment is carried out at 600°C for 2 hours. The heating rate of the carbonization treatment is 1°C / min; the cooling rate is 1°C / min.

[0166] Negative electrode:

[0167] According to the mass ratio of negative electrode active material: conductive carbon black (SP): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 80:10:4:6, add appropriate amount of deionized water and mix to form a slurry, which is coated on copper foil, dried at 90°C in vacuum for 12 hours and rolled to form a negative electrode sheet.

[0168] Battery:

[0169] Metal lithium sheets were used as counter and reference electrodes, a 1 mol / L LiPF6 three-component mixed solvent of ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 volume ratio mixed solution was used as the electrolyte, and Celgard 2500 was used as the diaphragm. The cells were assembled into CR2032 button cells in an argon-filled inert gas glove box system.

[0170] Performance Testing

[0171] (1) Aperture test

[0172] The negative electrode active materials of the above embodiments and comparative examples were tested using a pore size tester and a BET pore size distribution test method. The pore size distribution data of the negative electrode active materials were obtained by DFT simulation analysis using the isothermal adsorption characteristic curve of nitrogen, and then the average pore size of the pores of the negative electrode active materials was obtained. The test results are shown in Table 1.

[0173] (2) Stability test

[0174] First, 0.1g of sample and 5mL of water were placed in a sealed test tube, and the test tube was connected to a gas collecting device; then, during the mixing process, the gas produced in the test tube during the entire reaction process was collected; finally, the collected gas was analyzed by gas chromatography to determine the composition of the gas. The gas composition mainly includes nitrogen and hydrogen. The smaller the proportion of hydrogen, the less reactive the material is with water and the better the stability of the material. The test results are shown in Table 1.

[0175] (3) Electrochemical test

[0176] The battery charge and discharge tests of the above-mentioned embodiments and comparative examples were carried out on the Land battery test system. The test temperature was maintained at 25°C in a constant temperature box, and the charge and discharge current was 0.5C. The charge and discharge voltage was limited to 0.01V~1.5V (vs.Li + / Li), the test results are shown in Table 1.

[0177] Table 1

[0178]

[0179]

[0180] As shown in Table 1, by comparing Examples 1 to 12 and Comparative Examples 1 to 2, it can be seen that the negative electrode active material provided in the present application improves the stability of the negative electrode active material, ensures the capacity performance of the battery, and improves the initial coulombic efficiency and capacity retention rate of the battery.

[0181] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0182] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A negative electrode active material, characterized in that: include: A resin-based carbon skeleton, the surface of which is provided with pores connected to the interior of the resin-based carbon skeleton; as well as The active material unit is arranged in the pores of the resin-based carbon skeleton, and the active material unit includes an -O-Li-Si structure connected to the pore wall surface and nickel metal particles located inside the pores.

2. The negative electrode active material according to claim 1, characterized in that The average pore diameter of the pores is 0.5 nm to 6 nm.

3. The negative electrode active material according to claim 1, characterized in that The resin-based carbon skeleton is a hard carbon material.

4. A method for preparing a negative electrode active material, characterized in that: The following steps are involved: S1, mixing resin monomer, nickel salt, silicon powder and initiator in a solvent, filtering and drying after reaction, to obtain a silicon-carbon material precursor; S2, mixing the silicon-carbon material precursor with lithium hydroxide in a solvent or a buffer solution with a pH of 8 to 10, filtering and drying after the reaction, to obtain a pre-lithiated silicon-carbon material precursor; S3, heat treating the pre-lithiated silicon-carbon material precursor, cooling it, and obtaining a negative electrode active material; Among them, the negative electrode active material includes a resin-based carbon skeleton and an active substance unit, the surface of the resin-based carbon skeleton is provided with pores connected to the interior of the resin-based carbon skeleton, the active substance unit is arranged in the pores of the resin-based carbon skeleton, and the active substance unit includes an -O-Li-Si structure connected to the surface of the pore wall and nickel metal particles located inside the pore.

5. The method for preparing the negative electrode active material according to claim 4, characterized in that: In the step S1, the mass ratio of the silicon powder to the resin monomer is (0.2:1) to (4:1); and / or, In the step S1, the mass ratio of the silicon powder to the nickel salt is (1:1) to (10:1); and / or, In the step S1, the reaction temperature is 100° C. to 150° C., and the reaction time is 3 h to 5 h.

6. The method for preparing the negative electrode active material according to claim 4, characterized in that: In the step S2, the mass ratio of the nickel salt to the lithium hydroxide in the silicon-carbon material precursor is (0.9:1) to (2:1).

7. The method for preparing the negative electrode active material according to claim 4, characterized in that: In step S3, the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed in sequence, the temperature of the pre-oxidation treatment is 150°C to 300°C, the temperature of the carbonization treatment is 550°C to 750°C, and the heating rate of the carbonization treatment is 1°C / min to 1.5°C / min; and / or, In the step S3, the cooling rate is 1°C / min to 2°C / min.

8. A negative electrode plate, characterized in that: The invention comprises the negative electrode active material according to any one of claims 1 to 3, or the negative electrode active material prepared by the preparation method according to any one of claims 4 to 7.

9. A battery, characterized in that: Comprising the negative electrode sheet as described in claim 8.

10. An electrical device, characterized in that: Comprising the battery as claimed in claim 9.